Effects of introduction of an inflammatory bowel disease nurse position on healthcare use. Issue 5 (11th May 2020) - Martinez-Vinson, Christine; Le, Sebastien; Blachier, Audrey; Lipari, Maud; Hugot, Jean-Pierre; Viala, Jerome
Abstract : Objective: Inflammatory bowel diseases (IBDs) are chronic relapsing remitting diseases which potentially result in hospitalisation, requiring long-term outpatient follow-up, ideally by a dedicated, multidisciplinary team. In this team, the IBD nurse is the key point of access for education, advice and support. The aim of this study was to assess the impact of introduction of an IBD nurse position on healthcare use and costs in a tertiary IBD centre. Methods: An IBD nurse was instituted in September 2017 in our multidisciplinary IBD team. We compared differences in healthcare use 1 year before and 1 year after the introduction of an IBD nurse position for all the patients with a confirmed diagnosis of IBD attending the Robert Debre Hospital via two information sources: Programme de Médicalisation des Systèmes d'Information and Centre des Maladies Rares. Results: 252 patients (78.5% of patients with IBD followed up in our centre) were included in the patient education programme. After the introduction of an IBD nurse position, fewer patients were hospitalised for a flare, with less hospital stays: 56 before vs 28 after (p=0.002). An estimated saving of €35 070 was achieved through the decrease of hospitalisations for flare. More patients were also hospitalised for diagnosis: 32 hospitalisations before vs 54 hospitalisations after (p=0.001). All other hospitalisation categories were comparable, and the same reasons for hospitalisation were found before and after. Conclusion: This study demonstrates that the IBD nurse position reduces hospital admissions. Instead of the traditional model, the IBD nurse provides accessible advice and allows patients to be outpatients.